IDENTIFYING STUDENTS’ ABILITY IN LISTENING SHORT CONVERSATION - Lestari, Yunda; Lestari, Dewi (UNIVERSITAS TRIDINANTI PALEMBANG, 2017)
ABSTRACT: This study was aimed at identify the students’ ability and factors influence the ability in listening short conversation. Thisstudy used descriptive method.The population of this study was all students of first semester of English Education Study Program, Teacher Training and Education Faculty, Baturaja University with the total number were 60 students in academic year 2016/2017 and the sample was 40 students which are chosen by using slovin formula. The data obtained through listening test and close ended questionnaire and were analyzed by using descriptive analysis technique.The result of the study showed that there were 18 students (45%) at the very good level, 10 students (25%) at good level, 8 students (20%) at average level, and 4 students (10%) at poor level but based on the table of the score range and percentage at all. They were in very good level. The result of the questionnaire showed the factors that influence most the students’ ability in listening short conversation were: teacher employed under short conversation material taught to students and facilities provided by the university support fot teaching and learning process of listening.Key words: identifying, listening, short conversation